Gambaran Faktor Internal dan Faktor Eksternal dengan Kelelahan Kerja pada Perawat Rumah Sakit Umum Daerah Dr. Soeroto Ngawi - Muhammad Nur Ozim Ridho Purnomo; Lathiifah Amalia Rihtianti (Media Gizi Kesmas, 2024)
Background: Fatigue is a combination of decreased mental and physical function resulting in decreased work effectiveness and efficiency. The presence of fatigue can lead to a decrease in work productivity, the occurrence of work accidents, and decreased work motivation. The purpose of this study was to analyze the relationship of individual characteristics, physical workload, mental workload, working period, work shifts, and work stress with work fatigue in nurses of Dr. Soeroto Ngawi Regional General Hospital. Objectives: Analyzing relationship individual characteristics, physical and mental workload, length of work, work shifts, and work stress with fatigue. Methods: Observational with a cross-sectional research plan. The population in this study were all nurses at Regional General Hospital Dr. Soeroto Ngawi, numbering 211 people. The sample used in this research was 69 nurses taken using the probability sampling method with the proportional stratified random sampling technique. The variables studied were the worker’s internal factors (age, gender, nutritional status, marital status, work stress) and the workers’ external factors (physical workload, mental workload, length of service, work shifts). Results: There is a significant relationship between mental workload (r = 0.024, p = 0.271), physical workload (r = 0.042, p = 0.246), and work stress with work fatigue (r = 0.000, p = 0.449). Meanwhile, the work shift variables, age, gender, length of service, marital status, and nutritional status do not have a significant relationship to work fatigue in nurses at the Dr. Regional General Hospital. Soeroto Ngawi. Meanwhile, the work shift variable (r= 0.913, p = -0.013), age (r= 0.089, p = 0.206), gender (r= 0.19, p = – 0.16), length of service (r= 0.211, p = 0.153), marital status (r= 0.774, p = 0.035), and nutritional status (r=0, p = 0.035) did not have a significant relationship with work fatigue in nurses at the Dr. Regional General Hospital. Soeroto Ngawi. Conclusions: The study's conclusion was that age, gender, length of service, marital status, and nutritional status had no significant association with work fatigue in nurses. However, physical workload, mental workload, and work stress in nurses have a significant relationship. Advice for the company is to provide consumption to nurses so that the nurse's energy intake is met, pay attention to the suitability of the number of nurses with the number of patients treated, hold regular medical check-ups, and regular psychological counseling and psychiatric tests.